Physicians Treating Physicians: Relational and Informational Advantages in Treatment and Survival - Stacey H. Chen; Jennjou Chen; Hongwei Chuang; Tzu-Hsin Lin (Institute of Labor Economics (IZA), 2023)
We use the medical specialties of physician-patients with advanced cancer to study the role of knowledge versus networks in treatment choices and patient survival by matching comparable patients with doctors and admission periods to control unobserved doctor quality. Physician-patients are less likely to have surgery, radiation, or checkups and more likely to receive targeted therapy, spend more on drugs, enjoy a higher survival rate, and spend less on coinsurance than non-physician-patients. Knowledge mechanisms play a crucial role because the network effect explains some, but not all, patterns. For less informed physician-patients, possessing a network is equivalent to reducing medical knowledge.
Keywords: D83; I11; J44; 330; physician quality; social ties; communication; information